The generation of the student movement in Colombia. 1910-1924 - Soto Arango, Diana Elvira; Rivadeneira Vargas, José Antonio; Duarte Acero, Jorge Enrique; Bernal Villate, Sandra Liliana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this paper focuses on analyzing two student leaders, who lived the centennial period of the American independence, and simultaneously they also experienced the time of the Colombian student movement and the incidence of Cordoba´s one in this Latin American region. We refer to Luis López de Mesa (1884-1967), centenary generation: and Germán Arciniegas (1900-1999), generation of new leaders. The historical period covers from 1910 to 1924 corresponding to the first and second Colombian student Congress. From the political history are analyzed these two student leaders, who occupied the ministry of education under liberal governments. Both were dedicated to university teaching and were characterized by their contributions to journalism and their new approaches towards a reform of the Colombian university. Their conceptions on education and their university proposals are studied here from the perspective of the student movements and especially from the features adopted from Cordoba´s Movement in Colombia. The comparative methodology was used for this study and is based mainly on primary sources